Indigenous graphic communication systems: a theoretical approach - Mikulska, Katarzyna, editor; Offner, Jerome A., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2019)
Challenges Western academic views on what writing is and explores how these concepts can be improved by analyzing the sophisticated graphic communication systems found in Central Mesoamerica and Andean South America. Exploring and rejecting the Western notion that writing exists only to record the chain of speech.--Provided by publisher.
Introduction: indigenous graphic communication systems: a theoretical approach / Katarzyna Mikulska -- On the classification of graphs in Central Mexican pictorial writing / David Charles Wright-Carr -- The system of graphic communication in the Central Mexican divinatory codices from the functional perspective / Katarzyna Mikulska -- "The "law of the series": a proposal for the decipherment of Aztec ritual language / Danièle Dehouve -- Sacrifice in the Codex Borgia: examples from an inventory of phrases / Angélica Baena Ramírez -- Clothes with metaphorical names and the representation of metaphors in the costumes of the Mexican gods / Loïc Vauzelle -- What lies beneath: generating Mesoamerican media surfaces / Jerome A. Offner -- Traces of orality in the Codex Xolotl / Katarzyna Szoblik -- On the iconic nature of Tocapus and other framed motif units / Christiane Clados -- Geometric motifs in rock art as a system of visual communication / Stanisław Iwaniszewski -- Status markers in Moche iconography / Janusz Z. Wołoszyn -- Hieroglyphs of virtue and vice: on the interplay of writing and iconography / Gordon Whittaker -- An approach to anthroponymic glyphs in Nahuatl writing contained in El Libro de los Tributos de San Pablo Teocaltitlan or the Codex Valeriano / Juan José Batalla Rosado and Miguel Ángel Ruz Barrio -- The making of academic myth / Michel R. Oudijk.
Keywords: Indians of Mexico -- Languages -- Writing; Indians of Central America -- Languages -- Writing; Indians of South America -- Andes Region -- Languages -- Writing; Picture-writing -- Mexico; Picture-writing -- Central America; Picture-writing -- Andes Region; Visual communication -- Mexico; Visual communication -- Central America; Visual communication -- Andes Region